Iridoid glucosides from Wendlandia ligustroides (Boiss. &Hohen.) Blakelock - İhsan Çalış; Ayham Weas; Hasan Soliman Yusufoğlu; Ali A. Dönmez; Søren R. Jensen (Elsevier, 2020)
Eight iridoid glucosides were reported from the aerial parts of Wendlandia ligustroides. 10-deoxygeniposidic acid (1), 7-deoxygardoside (2), geniposidic acid (3), 7-deoxy-8-epi-loganic acid (4), deacetyl-daphylloside (5), scandoside methyl ester (6), 6-O-methyl-deacetyl-daphylloside (7), 6-O-methyl-scandoside methyl ester (8). Compounds 3 - 8 were isolated as a pure form while 1 and 2 as a mixture. The structures of the compounds 1 - 8 were established by spectroscopic methods including 1D-NMR (1H NMR, 13C NMR, DEPT-135), 2D-NMR (COSY, NOESY, HSQC, HMBC) and HRMS.